Does Gender of Administrator Matter? National Study Explores U.S. University Administrators' Attitudes About Retaining Women Professors in STEM - Williams, Wendy M.; Mahajan, Agrima; Thoemmes, Felix; Barnett, Susan M.; Vermeylen, Francoise; Cash, Brian M.; Ceci, Stephen J. (Frontiers in Psychology, 2017)
Omnipresent calls for more women in university administration assume these women will prioritize using resources and power to increase female representation, especially in STEM fields where women are most underrepresented. However, empirical evidence is lacking for systematic differences in female versus male administrators’ attitudes. Do female administrators agree on which strategies are best, and do men see things differently? To answer this question, we explored United States college and university administrators’ opinions regarding policies, strategies, and structural changes in their organizations designed to increase women professors’ representation and retention in STEM fields. A comprehensive review of past research yielded a database of potentially-effective, recommended policies (e.g., increasing emphasis on teaching, service, and administration during promotion reviews; stopping the tenure clock for childbearing; providing on-campus childcare; couples-hiring; sharing tenure lines; having more women chair search committees; setting gender quotas for promotion). A survey based on these recommended policies was sent to provosts, deans, associate deans, and department chairs of STEM fields at 96 public and private research universities (formerly called R1s) across the U.S. These administrators were asked to rate the quality and feasibility of each recommended policy; 474 provided data, of which 334 contained complete numerical data used in the analyses, so our results are based on a large, geographically diverse group of administrators at research universities. Our data revealed that female administrators perceived the 44 strategies to be higher in quality overall than did male administrators--but not higher in feasibility--with 9 policies perceived differently when rated by women versus men administrators, after imposing conservative statistical controls. There was broad general agreement on the relative rankings of the 44 policies in terms of their perceived quality. Overall, our national survey of U.S. administrators supported the assertion that placing women in administrative roles creates greater emphasis on the importance of enacting policies to attract and retain women in STEM. Topics of disagreement between women and men regarding strategy quality are important focuses of future policy and planning, because female administrators may have insights into how to retain women professors that male administrators do not share.